Evolution of eligibility criteria for diffuse large B‐cell lymphoma randomised controlled trials over 30 years. (14th April 2021) - Loh, Zoe; Salvaris, Ross; Chong, Geoffrey; Churilov, Leonid; Manos, Kate; Barraclough, Allison; Hawkes, Eliza A.
Summary: Eligibility criteria for randomised control trials (RCT) in diffuse large B‐cell lymphoma (DLBCL) may be becoming increasingly strict. In this analysis, 42 first‐line phase III RCTs enrolling DLBCL patients since 1990 were identified from PubMed and clinicaltrials.gov . Changes in 31 individual eligibility criteria were assessed using three pre‐defined eras [(1) 1993–2005; (2) 2006–2013; and (3) 2014–2020]. The presence of 15/31 criteria increased significantly over time, and the total number of criteria per study also increased over time [median Era 1: 14·5, interquartile range (IQR) 12·6–16·4; Era 2: 21, 18·8–23·3; Era 3: 23, 21–25; P < 0·001]. When each trial's eligibility criteria were applied to 215 consecutive patients from an institutional database treated between 2010 and 2020, a median of 57% (IQR 47–70) of patients were hypothetically eligible for trial enrolment. The median percentage of patients eligible was 68% (56–91), 54% (37–81) and 47% (38–82) for Era 1, 2 and 3 respectively ( P = 0·004). Phase III front‐line DLBCL trial criteria have become increasingly restrictive over the last three decades, resulting in a diminishing proportion of trial‐eligible patients, with less than 50% of our patients eligible for modern‐era studies. This potentially impacts generalisability of recent trial results and will likely limit recruitment to ongoing studies.